Sociological Research Design of Families Under Migration - Juozeliūnienė, Irena (Sociologija. Mintis ir veiksmas, 2013)
The aim of the article is introduce the research design of families affected by migration. The author argues that multidimensional family study from the perspective of family and kin resources, memory discourses, family doing and displaying practices, as well as coping with hardships requires mixed methods research. Research paradigm and theoretical model are discussed, methodological decisions are introduced, it is explained that triangulation is treated as one of the leading methodological decisions of the research design. The author discloses the possibilities of pragmatic approach and discusses triangulation of theories, methods, as well as data. Symbolic interactionism constitutes the main theoretical perspective of the research study, while Reuben Hill’s family change model is treated as conceptual axis of research. The aim of methodological solutions discussed in the article is to theorize family change by means of ideas of symbolic interactionism, theoretical construct of solidarity, personal networks and conceptions of family practices. The working concept of family and analytical model of family research, as well as the guidelines of family-state relations are delineated.